Screening for adenylosuccinate lyase deficiency using tandem mass spectrometry analysis of succinylpurines in neonatal dried blood spots - Zikanova, Marie; Krijt, Jakub; Skopova, Vaclava; Krijt, Matyas; Baresova, Veronika; Kmoch, Stanislav (Clinical biochemistry, 2015)
OBJECTIVES: Stable isotope dilution coupled with liquid chromatography-tandem mass spectrometry (LC-MS/MS) is the sensitive method for screening for various inherited metabolic disorders using dried blood spots (DBSs). We present a method for LC-MS/MS determination of succinyladenosine (SAdo) and succinylaminoimidazole carboxamide riboside (SAICAr), biomarkers for adenylosuccinate lyase deficiency (dADSL), in DBS. DESIGN AND METHODS: SAICAr and SAdo were separated on a Symmetry-C18 column and detected using positive electrospray ionisation in selected reaction monitoring mode. The quantification was performed using the isotopically labelled internal standards SAdo-(13)C4 and SAICAr-(13)C4, which were prepared via ADSL-catalysed reactions of fumarate-(13)C4 with adenosine monophosphate and aminoimidazole carboxamide ribotide, respectively, and subsequent alkaline phosphatase-catalysed dephosphorylation of the resulting products. RESULTS: The detection of SAICAr and SAdo in DBS was linear over the range of 0-25μmol/L. The respective intra-assay and inter-assay imprecision values were less than 10.7% and 15.2% for SAICAr and 4.7% and 5.7% for SAdo. The recoveries from DBS spiked with different concentrations of SAICAr and SAdo were between 94% and 117%. The concentrations of SAICAr and SAdo were higher in the archived DBS from dADSL patients (SAICAr, 0.03-4.7μmol/L; SAdo, 1.5-21.3μmol/L; n=5) compared to those of the control subjects (SAICAr, 0-0.026μmol/L; SAdo, 0.06-0.14μmol/L; n=31), even after DBSs from dADSL patients were stored for 2-23years. CONCLUSIONS: We developed and validated a method of succinylpurine analysis in DBS that improves selective screening for dADSL in the paediatric population and may be used for retrospective diagnosis to aid the genetic counselling of affected families.
Keywords: Adenylosuccinate Lyase; Purine-Pyrimidine Metabolism, Inborn Errors; Adenylosuccinate lyase deficiency; Reference Standards; Limit of Detection; limita detekce; Tandem mass spectrometry; adenosin; referenční standardy; Aminoimidazole Carboxamide; Ribonucleosides; Infant, Newborn; test suché kapky krve; aminoimidazolkarboxamid; ribonukleosidy; novorozenec; Adenosine; Humans; Screening; izotopy uhlíku; Tandem Mass Spectrometry; adenylsukcinátlyasa; DBS; Purine metabolism; Carbon Isotopes; chromatografie kapalinová; Autistic Disorder; autistická porucha; Dried Blood Spot Testing; tandemová hmotnostní spektrometrie; Chromatography, Liquid; LC–MS/MS; lidé; Dried blood spots; poruchy metabolismu purinů a pyrimidinů